Obama and China's rise : an insider's account of America's Asia strategy - Bader, Jeffrey A.; Brookings Institution (Washington, D.C. : Brookings Institution Press, 2012)
"Detailed evaluation from an insider of the Obama administration's efforts, between 2009 and spring 2011, to develop a stable relationship with China while countering China's rise by reinforcing and initiating relationships with other nations in the region"--Provided by the publisher.
Prologue. The candidate and the campaign -- Asia policy : the big picture -- Laying the foundation : Secretary Clinton visits Asia -- China : getting started -- North Korea : breaking the pattern -- Japan : from LDP to DPJ Rule -- China : the Obama visit and the Climate Change Conference -- Year two : dealing with an assertive China -- Tensions in Korea -- Building stronger ties with Southeast Asia -- China's push into other maritime areas -- The road to Hu Jintao's visit to the United States -- Dealing with multiple disasters in Japan -- Looking back, looking ahead.
Includes bibliographical references (p. 151-162) and index.
Keywords: Obama, Barack -- Political and social views; United States -- Foreign relations -- China; China -- Foreign relations -- United States; United States -- Foreign relations -- 2009-; United States -- Foreign relations -- Asia; Asia -- Foreign relations -- United States